Tafsir-Tafsir Modern dan Kontemporer Abad Ke-19-21 M - Dinni Nazhifah (Jurnal Iman dan Spiritualitas, 2021)
Al-Qur’an always puts forward the opinion or motto "shalih fii kulli zaman wa makan", in the sense that it is not fair to just accept what is expressed literally, but tries to see the context and meaning behind the verses of the Al-Qur’an. In other words, what you want to look for is the "spirit" or moral message of the Qur'an itself. Modern and contemporary interpretations are always encouraged to adapt to the progress that may be the main factor in giving birth and increasing the response of interpreter translators. This article tries to describe the state of some of the modern and contemporary exegetical works that developed in the 19-21 century AD. At the end of the discussion, the writer concludes that the modern and contemporary are dominated by education based on the philosophy of the Qur'an, the Qur'an and natural history, newspapers and the actual Muslim dailu. Here the author also concludes that modern and contemporary interpretations contain strong meanings for the Islamic ummah, both daily problems, as well as objective concrete support for the development of human knowledge.